2016
DOI: 10.1007/s10943-016-0258-z
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of Afterlife Belief Scale for Muslims

Abstract: The purpose of this study was to develop a scale in Urdu language for measuring different dimensions of afterlife belief. The scale was subjected to exploratory and confirmatory factor analysis on a sample of 504 individuals (235 men and 269 women) recruited from different cities in the Punjab, Pakistan. After exploratory and confirmatory factor analysis, 16 items were retained with three well-defined factor structures of afterlife belief: positive, negative, and extinction. The alpha coefficients of the subsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Analysis of the Jordanian data revealed gender differences, and it was found that the level of CTAP belief was higher among females. This is somewhat consistent with previous studies that found that females scored higher on Islamic negative afterlife beliefs (Ghayas and Batool 2017). No gender differences were found among the Malaysian sample.…”
Section: Discussion and Directions For Future Researchsupporting
confidence: 92%
“…Analysis of the Jordanian data revealed gender differences, and it was found that the level of CTAP belief was higher among females. This is somewhat consistent with previous studies that found that females scored higher on Islamic negative afterlife beliefs (Ghayas and Batool 2017). No gender differences were found among the Malaysian sample.…”
Section: Discussion and Directions For Future Researchsupporting
confidence: 92%
“…The positive correlation between AFE and RBA supports the results of previous studies, which found a negative link between negative beliefs about the afterlife and mental health (Flannelly 2017;Ghayas and Batool 2017;Ghorbani et al 2008). However, the findings contradict studies suggesting that fear of the afterlife is one of the most important functions of religion in activating self-control (Baumeister et al 2010;Kim-Spoon et al 2015;Laurin et al 2012;McCullough and Willoughby 2009;Pirutinsky 2014;Rounding et al 2012), promoting positive social behavior (Saleam and Moustafa 2016), and reducing levels of crime (Shariff and Rhemtulla 2012).…”
Section: Discussion and Directions For Future Researchsupporting
confidence: 89%
“…For example, the subject of afterlife reward and punishment is a major theme found throughout the Qur'an, the main source text of the Islamic religion (Dastmalchian 2017; Lange 2016; Murata and Chittick 1994). Currently, studies have begun to pay attention to the importance of understanding the details of afterlife beliefs concerning reward and punishment in order to understand the psychological and social impact of these beliefs (Ghayas and Batool 2017; Wrocawska-Warchala and Warchala 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Adherents to religions which teach that an affiliation with one's own faith is crucial for a happy destiny in the afterlife might have a separate motive for staying within this religion and keeping a proper distance from the possible truths of other worldviews. For some Muslims and Christians, thoughts of afterlife might be an important motivation for holding on to a firm belief and actively rejecting possible doubts (Ghayas and Batool 2017).…”
Section: The Certainty Dimension: Doubtful Versus Convincedmentioning
confidence: 99%